Urinary excretion study following consumption of various poppy seed products and investigation of the new potential street heroin marker ATM4G. Issue 3 (29th September 2016) - Maas, Alexandra; Krämer, Michael; Sydow, Konrad; Chen, Pai‐Shan; Dame, Torsten; Musshoff, Frank; Diehl, Bernd W.K.; Madea, Burkhard; Hess, Cornelius
Abstract : Discrimination between street heroin consumption and poppy seed ingestion represents a major toxicological challenge in daily routine work. Several difficulties associated with conventional street heroin markers originate from their versatile occurrence in various poppy seed products and medications, respectively, as well as to small windows of detection. A novel opportunity to overcome these hindrances is represented by the new potential street heroin marker acetylated‐thebaine‐4‐metabolite glucuronide (ATM4G), originating from thebaine during street heroin synthesis followed by metabolic reactions after administration. In this study, urine samples after consumption of different German poppy seed products and urine samples from subjects with suspicion of preceding heroin consumption were tested for ATM4G, 6‐AC (6‐acetylcodeine), papaverine, noscapine, 6‐MAM (6‐monoacetylmorphine), morphine, and codeine. Neither 6‐AC and 6‐MAM nor ATM4G but morphine and codeine could be detected in urine samples following poppy seed ingestion. As well, neither papaverine nor noscapine could be observed even after consumption of poppy seeds containing up to 37 µg noscapine and up to 9.8 µg papaverine, respectively. Concerning the urine samples with suspicion of preceding heroin consumption, ATM4G could be detected in 9 of 43 cases. By contrast, evidence of 6‐AC and 6‐MAM, respectively, could only be seen in 7 urine samples. In conclusion, ATM4G should be measured additionally in cases requiring discrimination of street heroin consumption from poppy seed intake. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Urine samples after consumption of different German poppy seed products and urine samples from subjects with suspicion of preceding heroin consumption were tested for ATM4G and further conventional street heroin markers. ATM4G could not be detected in urine samples following poppy seed ingestion. Though, proof of ATM4G could be provided in 9 of 43 urine samples from individuals with suspicion of preceding heroin consumption. By contrast, evidence of 6‐AC and 6‐MAM, respectively, could only be seen in seven urine samples.